EKSPLORASI DAMPAK PERUBAHAN MANUAL DESAIN PERKERASAN JALAN (MDPJ) 2017 KE 2024 MENGGUNAKAN PROGRAM KENPAVE - Hadi, Muhamad Abdul (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2024)
his study explores the impact of changes in the Manual for Pavement Design (MDPJ) from the 2017 edition to the 2024 edition, published by the Directorate General of Highways (DJBM) in May 2024, using the same secondary data as a comparative approach. The secondary data used in this research is from the Prambanan ”“ Piyungan road section in 2023. This exploration is considered crucial to identify how modifications in the latest design guidelines may influence the final outcomes in road planning, particularly in pavement performance.Using the KENPAVE program, the performance comparison between the two pavement designs is assessed based on predicted vulnerability levels to rutting (Nr), fatigue cracking (Nf), and permanent deformation (Nd). The first predicted failure value is then selected and used as a reference in this study. The comparative analysis results (based on the current study”™s secondary data) indicate that pavement design based on MDPJ 2024 has a lower vulnerability value than MDPJ 2017, with a percentage difference of 5.5%. This study confirms that the updates in the latest design guidelines contribute to improving pavement performance. The findings of this research are expected to support the effective and sustainable implementation of MDPJ 2024 in Indonesia.